Pembuatan Karakter Animasi “Rani” Sebagai Contoh Fenomena Gegar Budaya Mahasiswa Asal Pulau Sumatera di Pulau Jawa - Yulianti, Shakila Dwi; Rachman, Anung; Kurniawan, Rendya Adi (Universitas Komputer Indonesia, 2023)
Culture shock is a phenomenon that often occurs among migrants. The high mobility in Indonesia causes people to move from one region to another, hence the phenomenon of culture shock is inevitable. Therefore, the phenomenon of culture shock cannot be avoided. In this context, the character of an immigrant from Sumatra who experiences the phenomenon of culture shock is created as an animated character. This animated character with the theme of culture shock is is adapted to the background and cultural identity that is used as a visual attribute of the character. Character creation pays attention to character features that can be remembered by the audience, These features include the identity, hobbies, activity patterns and preferences of an animated character. character. In addition, this animated character is introduced with animated media featuring simple activities played by this character. The animation was produced using Adobe Animate CC software with frame to frame technique and VSDC Video editor for compositing stage